Cost-effectiveness analysis for the use of serum antiepileptic drug level monitoring in children diagnosed with structural-metabolic epilepsy - Saliha, Muhammad R.M.; Bahari, Mohd. Baidi; Shafie, Asrul Akmal; Ahmad Hassalic, Mohamed Azmi; Baderaldeen , Omer Qutaiba; Abd, Arwa Y.; Ganesan, Vigneswari M. (Elsevier Inc., 2012)
Treatment with antiepileptic drugs is commonly guided by serum level monitoring. Such monitoring requires expensive laboratory equipment and products. However, well-conducted studies on the cost-effectiveness of therapeutic drug monitoring for antiepileptic drugs are lacking particularly in patients with structural-metabolic epilepsy. The study aims to assess the cost-effectiveness of serum level monitoring services in the management of children with structural-metabolic epilepsy during the first year of diagnosis. A retrospective cost-effectiveness analysis was conducted from the provider perspective. It included patients attended a paediatric neurology clinic. The effectiveness measures used in this analysis were the number of patients that achieved ≥50% reduction in seizure frequency, and the number of patients with 3-month seizure free. Medical records of the patients were reviewed for the required information. Medical chart/billing data obtained from the hospital were collected to estimate the resources used (One Malaysian Ringgit MYR is equivalent to 0.31 USD). The recruited children were followed for one year following their first visit. The average cost effectiveness ratio for the monitored patients (MYR 2735 per patient that achieved a ≥50% reduction in seizure frequency) was lower than that for non-monitored patients (MYR 2921 per patients that achieved a ≥50% reduction in seizure frequency), with incremental cost-effectiveness ratio of MYR 2357 per one additional patient that achieved a ≥50% reduction in seizure frequency. The average cost effectiveness ratios for monitored and non-monitored group were MYR 8279 and MYR 6433 per patient with a 3-month seizure-free period, respectively, with incremental cost-effectiveness ratio of MYR 29,666 per one additional patient with a 3-month seizure-free period. In terms of the effectiveness measures used, serum level monitoring of antiepileptic drugs was found to be cost-effective. However, the incremental cost-effectiveness ratio was found to be sensitive to the cost of management.